HISTOPATHOLOGICAL FEATURES OF DENOSUMAB TREATED GIANT CELL TUMOURS OF BONE A SINGLE INSTITUTIONAL EXPERIENCE AT A TERTIARY CARE CENTER, KARACHI - Mansoor Ali, Salima; Yaqoob, Nausheen; Aftab, Kanwal; Tauseef, Samar; Ahmed, Syed Kamran; Jilani, Syed Ali Anwar; Jamal, Saba (Journal of Ayub Medical College Abbottabad, 2022)
Background: Giant cell tumour (GCT) is a primary benign, locally aggressive bone tumour. Treatment is surgical however, denosumab has been increasingly used as a treatment in recurrent or unresectable locally advanced GCT because of its effect in reducing tumour size. Denosumab treated GCT can exhibit a wide array of histopathological features resulting in diagnostic problems for pathologists. Our study aimed at identifying these histopathological features to aid pathologists in reaching a correct diagnosis. Methods: Our study included 20 patients of biopsy-proven GCT cases treated with denosumab. We received specimens for histopathological examination in our institution from January 2018 to March 2020. The demographic and clinical data of these patients were retrieved from the Health Management Information System (HMIS). The slides were retrieved and studied for histopathological changes. Results: The mean age of patients in our study was 29.5 years. There were 11 males and 9 females. Distal radius was most commonly involved bone. On histopathological examination, ovoid to spindle mononuclear stromal cells were seen. Total absence of osteoclast like giant cells was seen in 10 (50%) cases, whereas 3 (15%) cases showed a marked reduction in osteoclast like giant cells. Conclusion: Denosumab treated GCT of bone can exhibit a wide spectrum of histopathological features. Pathologists need to be mindful of these features. Correlation of histopathological findings with clinical history and radiological features is important to prevent erroneous diagnosis. Treatment history of patients with denosumab is essential as incorrect diagnosis can be made if the history of denosumab treatment is not provided.